Design and analysis of frame scaffolding capacity using thickness and material as variables / Jegathis Murugesu - Jegathis, Murugesu (2017)
This thesis presents a comprehensive investigation of the design and analysis, based by variable thickness and material of steel frame scaffolding systems. Support scaffolding systems are used to provide temporary support to timber formwork systems, reinforcement, concrete, workmen and equipment, during the construction of permanent structures such as buildings and bridges. Conventional steel frame or called as a frame scaffold steel are the focus of the thesis. This thesis includes the collection and statistical analysis on thickness and material especially on material of JIS 3444 STK 500 and JIS 3444 STK 400 of load effects occurring as a result of after load test on steel frame scaffolding. A comprehensive series data based have been collected before test and purely test hand on tests, three major consideration have been taken which is tensile strength, yield strength and elongation based on chosen material.. This load capacity test exercise also provides statistical data for modelling error. The higher tensile strength analysis to determine the suitable material with right thickness for steel frame scaffolding. The research showed that strength of scaffolding is not just depends on steel frame but also depends on thickness which in this case we use 2.3mm and 2.5mm of the scaffolding system.